Roosts and migrations of swallows - Winkler, David W. (2006)
Swallows of the north temperate zone display a wide variety of territorial behaviour during the breeding season, but as soon as breeding is over, they all appear to adopt a pattern of independent diurnal foraging interleaved with aggregation every night in dense roosts. Swallows generally migrate during the day, feeding on the wing. On many stretches of their annual journeys, their migrations can thus be seen as the simple spatial translation of nocturnal roost sites with foraging routes straightening out to connect them. However, swallows that must make long journeys over ecological barriers clearly fly at night as well as in the day, and many suggestions indicate that there is considerable complexity in the altitude and bearing of flights even during the day. There are especially intriguing indications that much swallow migration may take place high out of sight of ground observers with movements near the ground often associated with foraging in passage. Provided that roost sites can be reliably found, swallow migration can be extremely flexible, and there are interesting contrasts in the biogeography and phenological flexibility of swallows compared to other passerine birds. Even within the swallows, there is considerable interspecific and intraspecifc variability in the distances of their annual migrations, and we are only just beginning to understand the biological causes and consequences of this variation. The profusion of Doppler weather radar stations in the eastern United States has allowed the characterization in considerable detail of the North American distributions of Tree Swallows (Tachycineta bicolor) and Purple Martins (Progne subis) throughout the non-breeding season. Evaluating the relative roles of movements and mortality in creating these patterns remains an important challenge for further research.